ショウワキチ マイクロパルスライダー ニヨッテ カンソク サレタ ヒチケイセイ カンセイ ジュウリョクハ キゲン ノ ナンキョク キョクセイソウケン クモ - 柴田, 隆; シバタ, タカシ; 佐藤, 薫; サトウ, カオル; 小林, 拓; コバヤシ, ヒロシ; 矢吹, 正教; ヤブキ, マサノリ; 塩原, 匡貴; シオバラ, マサタカ; Shibata, Takashi; Sato, Kaoru; et al. (2010)
P(論文) 昭和基地に設置されたマイクロパルスライダー(MPL)により下部成層圏高度領域において極成層圏雲(PSC)が観測された.ラジオゾンデで観測されたPSCの出現高度における気温は氷の露点温度より約4度低く,提唱されている氷粒子生成温度とほぼ一致している.また,PSCの散乱強度は十分大きく,このPSCは氷粒子からなるType IIと分類された.観測されたPSCは温度の高度分布に対応し,温度極小高度を中心にして縞状に存在している.出現高度は時間とともに1日あたり～ 2 km降下している.温度極小は約4 kmの幅で4箇所存在し,それぞれの温度極小高度にPSCが現れている.ラジオゾンデで観測された風向風速の高度分布の解析から,この温度極小が非地形性の慣性重力波によることが示された.この種の重力波がPSCの生成に重要な役割を果たしている可能性が示唆された.PSCの出現に必要な気温低下が地形に制限されないため,非地形性慣性重力波が南北両極上空のPSC粒子生成に広く寄与している可能性が示唆された. Type II Polar Stratospheric Clouds (PSCs) were observed by micropulse lidar (MPL) at Syowa Station in the Antarctic on 30 June and on 1 July 2001. The vertical profiles of the PSCs had a wavy structure that was synchronized with the temperature fluctuations. A wave analysis using radiosonde data shows that the wavy fluctuations were associated with an inertia gravity wave that was not forced by ground topography, but probably by spontaneous adjustment in association with synoptic-scale wave-breaking processes in the upper troposphere. It is suggested that the observed PSCs were generated under the low-temperature conditions induced by these waves and that such gravity waves generated by spontaneous adjustment of large-scale fields can be more important to the formation of PSC particles, in both the Antarctic and Arctic stratospheres, than topographically forced gravity waves, because the former are not fixed to the ground topography. departmental bulletin paper